Treatment of diaphyseal femoral fractures with external fixation device - Litvishko, Valeriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Choice of the best method for treatment of patients with diaphyseal fractures of long bones is debated issue of modern traumatology. Objective: to improve methods of treatment of diaphyseal femoral fractures with using of external fixation apparatus’ (EFA) produced by PE «ORTOPAK» and to evaluate outcomes of their using. Methods: we treated 80 patients with 83 fractures of the femur. In 32 of them fracture of the femur was combined with fractures of other segments. In the majority of patients (65) we performed closed reduction of fragments by skeletal traction system for 5–7 days followed by fixation with EFA, and in 15 ones simultaneous closed reduction and fixation with EFA was done. In 3 cases there was necessity for open reduction of fragments. Results: terms of fixation with EFA were 10 weeks in 22 (27.5%) patients, to 16 weeks — in 38 (47.5 %), to 20 — in 14 (17.5 %), to 24 — in 5 (6.25 %), and to 30 — in 1 (1.25 %) patients. Nonunion was observed in 3 (3.75 %) patients. Conclusion: diaphyseal femoral fractures might be effectively treated with EFA of PE «ORTOPAK» production choosing an adequate method of fragments’ reduction.